From Comfort to Achievement: Does School Well-Being Foster Students’ Academic Motivation? - Suryanto, Edy; Dwi Ratnasari (SEUNEUBOK LADA: Jurnal ilmu-ilmu Sejarah, Sosial, Budaya dan Pendidikan, 2025)
Student well-being is increasingly recognised as a key determinant of academic success and overall student development. In this context, the present study aims to examine the impact of school well-being on students’ achievement motivation at the secondary education level. School well-being is conceptualised into four dimensions: physical and material conditions (Having), social relationships (Loving), self-actualisation (Being), and health. Using a quantitative approach, data were collected from 120 students randomly selected from public secondary schools in Salatiga City, Central Java. Multiple linear regression analysis revealed that the four dimensions of school well-being collectively accounted for 72.5% of the variation in students’ achievement motivation, indicating a strong positive relationship between perceived school well-being and students’ intrinsic academic drive. The remaining 27.5% is influenced by other external factors beyond the model. These findings highlight the importance of a holistic approach within school environments that prioritises students’ comprehensive well-being in order to enhance motivation and academic performance. This study contributes to the growing body of literature on student well-being by providing empirical evidence from a non-Western educational context and suggests policy and practical implications for schools aiming to boost student motivation through well-being-centred strategies.